NATIONAL IDENTITY IN THE CONTEXT OF ENGLISH FOOTBALL DISCOURSE ANALYSIS - Marina Laskova; Yanna Belikova (Гуманитарные и юридические исследования)
The present article aims to analyze football discourse as an 'agent' of national identity reflecting nation's self-awareness through mass consciousness. The study highlights that since its inception football acted as an agent of national ideology, and the successes of national teams propelled the sense of patriotic and national unity. The competitive essence of this team game generates bright emotions and their manifestation displays the common features of national character. National identity can be produced, transformed and demounted through language, which is why the idea of national identity is realized through discourse. Based on the analysis conducted, the authors conclude that national identity is being reflected through football discourse following on from three key elements, which are the use of the pronoun 'we', spatial orientation and the 'friend-or-foe' opposition. Each of these elements represents a component of discourse practices explicating the peculiarities of national self-awareness of players, fans and the representatives of discourse community in general. At the same time, the authors note that football discourse is a secondary one, since the game has been associated with entertainment, rather than with primary social amenities.